Liver Transplantation in Hepatitis B Reactivation in a Patient With Active HIV Viremia. Issue 12 (29th December 2022) - Hegazy, Yassmin; Reif, Meagan; McGuire, Brenden M.; Cannon, Robert; Orandi, Babak; Shoreibah, Mohamed
ABSTRACT: Acute hepatitis B virus infection is a common contraindication to liver transplantation surgery in the setting of active HIV viremia. This is a case report of a patient with decompensated cirrhosis and acute renal failure in the setting of hepatitis B virus reactivation and active HIV viremia who underwent liver transplantation with sustained graft survival.